2017
DOI: 10.1371/journal.pone.0180673
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of ursodeoxycholic acid by lipopolysaccharide-stimulated inflammatory responses in RAW 264.7 macrophages

Abstract: PurposeThe aim of this study was to investigate the anti-inflammatory effects of Ursodeoxycholic acid (UDCA) in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages.MethodsWe induced an inflammatory process in RAW 264.7 macrophages using LPS. The anti-inflammatory effects of UDCA on LPS-stimulated RAW 264.7 macrophages were analyzed using nitric oxide (NO). Pro-inflammatory and anti-inflammatory cytokines were analyzed by quantitative real time polymerase chain reaction (qRT-PCR) and enzyme-linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 32 publications
(31 reference statements)
6
56
0
2
Order By: Relevance
“…(120) UDCA was also shown to reduce TNFα-induced IL-8 production by macrophages associated with a reduction in TNFα receptorassociated factor 2 (TRAF2) phosphorylation (121) and to reduce LPS-induced macrophage activation. (122)(123)(124) Although all cells in one organism possess the same genetic material, gene expression modulation through epigenetic modifications controlled by histone remodeling, transcription factors, miRNAs, and long noncoding RNAs results in a plethora of distinct cell types. Recent studies have highlighted that macrophages are not exempt from these epigenetic modifications because they directly affect the polarization state of macrophages.…”
Section: Spectra and Fluidity Of Macrophage Polarization Statesmentioning
confidence: 99%
“…(120) UDCA was also shown to reduce TNFα-induced IL-8 production by macrophages associated with a reduction in TNFα receptorassociated factor 2 (TRAF2) phosphorylation (121) and to reduce LPS-induced macrophage activation. (122)(123)(124) Although all cells in one organism possess the same genetic material, gene expression modulation through epigenetic modifications controlled by histone remodeling, transcription factors, miRNAs, and long noncoding RNAs results in a plethora of distinct cell types. Recent studies have highlighted that macrophages are not exempt from these epigenetic modifications because they directly affect the polarization state of macrophages.…”
Section: Spectra and Fluidity Of Macrophage Polarization Statesmentioning
confidence: 99%
“…Previous studies have used the model of ischemia-reperfusion injury to explore the inflammatory process and found that propofol exhibited antioxidant and anti-inflammatory effects [ 1 5 ]. Lipopolysaccharide (LPS) is the major cause of clinical fever, it is also the key factor that cause the shock, sepsis, cholera, and other diseases like adult respiratory syndrome, multiple organ failure, or the pathological processes [ 6 ]. Gram-negative bacteria are often used to induce inflammation in vitro, and studies have shown that LPS is a major component of the outer membrane of Gram-negative bacteria [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is the major cause of clinical fever, it is also the key factor that cause the shock, sepsis, cholera, and other diseases like adult respiratory syndrome, multiple organ failure, or the pathological processes [ 6 ]. Gram-negative bacteria are often used to induce inflammation in vitro, and studies have shown that LPS is a major component of the outer membrane of Gram-negative bacteria [ 6 ]. Studies have confirmed that high-mobility group box 1 (HMGB1) is a DNA-binding protein that maintains nucleosomal structures and regulates gene transcription, which is characterized by highly conserved proteins.…”
Section: Introductionmentioning
confidence: 99%
“…When surgical injury causes nerve damages, the microglia in the spinal cord and brainstem are activated by surface P2 receptors, chemokine receptors, and toll-like receptors (TLRs). The activated small microglia can release a series of inflammatory factors (IL-1β, IL-6, and TNF-α) that mediate neuroinflammatory responses, leading to central sensitization [27].…”
Section: Central Sensitizationmentioning
confidence: 99%